PERLINDUNGAN HUKUM KONSUMEN DALAM TRANSAKSI JUAL BELI MELALUI E-COMMERCE DITINJAU DARI PERSPEKTIF HUKUM PERDATA INDONESIA - Dinda Safira Devianda; Parlaungan Gabriel Siahaan; Dinda Ujung; Gresy Viarosa Saragih; Renata Sitohang; Yuliana Kristina Sinurat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of information technology has significantly transformed trading activities through electronic commerce (e-commerce). Online buying and selling transactions provide convenience and efficiency for society, but they also create various legal problems, particularly regarding consumer protection. Consumers often experience losses such as goods that do not match descriptions, fraud, delays in delivery, and misuse of personal data. This study aims to analyze the forms of consumer legal protection in ecommerce transactions from the perspective of Indonesian civil law, the legal regulation of online transactions, obstacles in consumer protection, and dispute resolution efforts. The research uses a normative legal research method with a statutory and literature approach by examining legal materials such as legislation, journals, and other relevant references. The results show that consumer protection in e-commerce transactions in Indonesia is regulated through the Civil Code, Law Number 8 of 1999 concerning Consumer Protection, and Law Number 11 of 2008 concerning Electronic Information and Transactions along with its amendments. However, the implementation of consumer protection still faces several obstacles, including weak supervision of digital business actors, lack of consumer legal awareness, and risks related to personal data security. Therefore, stronger legal enforcement, regulatory updates, and public legal education are needed to ensure legal certainty and justice for consumers in e-commerce transactions.